Novel Peptide Conjugates of Modified Oligonucleotides for Inhibition of Bacterial RNase P - Novopashina, Darya; Vorobyeva, Mariya; Nazarov, Anton; Davydova, Anna; Danilin, Nikolay; Koroleva, Lyudmila; Matveev, Andrey; Bardasheva, Alevtina; Tikunova, Nina; Kupryushkin, Maxim; Pyshnyi, Dmitrii; Altman, Sidney; et al. (Frontiers in Pharmacology, 2019)
Novel alternatives to traditional antibiotics are now of great demand for the successful treatment of microbial infections. Here, we present the engineering and properties of new oligonucleotide inhibitors of RNase P, an essential bacterial enzyme. The series of 2'-O-methyl RNA (2'-OMe-RNA) and phosphorylguanidine oligonucleotides were targeted to the substrate-binding region of M1 RNA subunit of the RNase P. Uniformly modified 2'-OMe RNA and selectively modified phosphorylguanidine oligonucleotides possessed good stability in biological media and effectively inhibited RNase P. Their conjugates with transporting peptides were shown to penetrate bacterial cells (Escherichia coli and Acinetobacter baumannii) and inhibit bacterial growth.